2015
DOI: 10.1159/000368856
|View full text |Cite
|
Sign up to set email alerts
|

Restoring SIRT6 Expression in Hutchinson-Gilford Progeria Syndrome Cells Impedes Premature Senescence and Formation of Dysmorphic Nuclei

Abstract: Objectives: Mice overexpressing SIRT6 live longer than wild-type mice while SIRT6 knockout mice exhibit similar degenerative phenotypes as individuals with Hutchinson-Gilford progeria syndrome (HGPS). Thus, we sought to test whether levels of SIRT6 are reduced in cells from individuals with HGPS and whether restored SIRT6 expression may impede premature aging phenotypes. Methods: Levels of endogenous SIRT6 and progerin in HGPS and normal fibroblasts were assessed by Western blotting and immunofluorescence. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…T2D metabolic defects are also ameliorated by increased activation of SIRT6, possibly through suppression of IGF1 signalling 92 . SIRT6 levels are decreased in patients with HGPS, and SIRT6 over-expression partially rescues the senescent phenotype of fibroblasts from patients with HGPS and extends the lifespan of wild-type male mice 101,102 .…”
Section: Cellular Metabolismmentioning
confidence: 98%
“…T2D metabolic defects are also ameliorated by increased activation of SIRT6, possibly through suppression of IGF1 signalling 92 . SIRT6 levels are decreased in patients with HGPS, and SIRT6 over-expression partially rescues the senescent phenotype of fibroblasts from patients with HGPS and extends the lifespan of wild-type male mice 101,102 .…”
Section: Cellular Metabolismmentioning
confidence: 98%
“…Intriguingly, recent studies have suggested that impaired heterochromatin maintenance due to reduced SIRT6 activity could contribute to pathogenesis of Hutchinson-Gilford Progeria Syndrome (HGPS), a human premature aging disorder [31]. HGPS patient cells express an abnormal Lamin A protein, a scaffold protein that is important for heterochromatin maintenance.…”
Section: Heterochromatin Silencing and Genome Maintenance In Aging Anmentioning
confidence: 99%
“…Recently, Lamin A was found to activate SIRT6-dependent histone deacetylation and ADP-ribosylation (see Box 1), but this function is lost in the HGPS mutant Lamin A protein [33]. Moreover, other work revealed that SIRT6 levels were reduced in HGPS cell lines, and SIRT6 re-expression in these cells attenuated their premature senescence [31]. It will be interesting to determine whether the underlying mechanisms involve SIRT6-dependent re-silencing of heterochromatin at pericentric or other genomic regions.…”
Section: Heterochromatin Silencing and Genome Maintenance In Aging Anmentioning
confidence: 99%
“…Suppression of SIRT6 protein levels mediates premature senescence-like phenotype in cells under H 2 O 2 -induced oxidative stress [99]. Premature cell senescence in Hutchinson–Gilford progeria syndrome (HGPS) and chronic obstructive pulmonary disease is linked with lower SIRT6 expression; its restoration remedies a number of senescence-linked traits, in the latter case through modulation of IIS–mTor signaling [100, 101]. The restoration of falling SIRT6 levels also rescues the diminished efficiency of DNA base excision repair in human foreskin fibroblasts from aged donors [102].…”
Section: Sirtuins In Agingmentioning
confidence: 99%